FISHing for bacteria in food – A promising tool for the reliable detection of pathogenic bacteria?. (April 2015) - Rohde, Alexander; Hammerl, Jens Andre; Appel, Bernd; Dieckmann, Ralf; Al Dahouk, Sascha
Abstract: Foodborne pathogens cause millions of infections every year and are responsible for considerable economic losses worldwide. The current gold standard for the detection of bacterial pathogens in food is still the conventional cultivation following standardized and generally accepted protocols. However, these methods are time-consuming and do not provide fast information about food contaminations and thus are limited in their ability to protect consumers in time from potential microbial hazards. Fluorescence in situ hybridization (FISH) represents a rapid and highly specific technique for whole-cell detection. This review aims to summarize the current data on FISH-testing for the detection of pathogenic bacteria in different food matrices and to evaluate its suitability for the implementation in routine testing. In this context, the use of FISH in different matrices and their pretreatment will be presented, the sensitivity and specificity of FISH tests will be considered and the need for automation shall be discussed as well as the use of technological improvements to overcome current hurdles for a broad application in monitoring food safety. In addition, the overall economical feasibility will be assessed in a rough calculation of costs, and strengths and weaknesses of FISH are considered in comparison with traditional and well-established detection methods. Highlights: Current detection methods of foodborne pathogenic bacteria have limitations. FISH represents a promising alternative to established techniques. FISH is a suitable tool for the specific and reliable detection of bacteria in food. Automation, standardization and validation of FISH are future challenges.